(untitled) (Philippines, 1984)
The book selects the papers presented on the workshop held at Banjarmasin, Kalimantin Selatin, Indonesia. The workshop identified new technologies that, by a concerted research effort, could be generated for the fragile environment of tidal swamps identified the problems unique to the tidal swamp areas
Keywords: Rice; Research,Congresses